Some Insights into Egypt’s History under the Reign of Maximinus Thrax (Mid-March / 25 March AD 235 – 10 May AD 238) - Ismail, Hanan M. I. (Hyperboreus, 2021)
This paper focuses on some aspects of Egypt’s history in the reign of Maximinus Thrax (Mid-March/25 March AD 235 – 10 May 238). The author argues that the economic repercussions and the political upheaval in Egypt were tightly interwoven with the beginning of the Third Century Crisis. The article surveys forty-three documents (papyri and ostraca), through which new ﬁndings regarding the history of Egypt can be attained.